Design of EtherCAT Slave Station Communication System Based on ZYNQ Processor - LI Yi; WANG Chengjie; SHI Shiyou; FU Jianguo (Kongzhi Yu Xinxi Jishu)
CANopen fieldbus is commonly used in wind power field, which current communication cycle is 10 ms and data volume is 96 bytes. Slow running speed and small amount of data transmitted make it cannot meet the growing demand for real-time communication on site. This paper presents an EtherCAT slave station communication system scheme, which uses ZYNQ7000 as slave processor to realize the function of application layer, uses LAN9252 controller for data interaction between data link layer and physical layer to realize high real-time data communication, uses VxWorks real-time operating system constructed by ZYNQ7000 processor to process periodic slave data. System data communication test is carried out by the EtherCAT test software and the test results show that the response time of the system does not exceed 13 μs, the packet loss rate is 0, the communication period can reach 3 ms, and the data volume is 360 bytes, indicating that the system has good real-time performance and stability, and can meet the requirements of equipment in wind power field.